Cryopreserved Fetal Liver Cell Transplants Support the Chronic Failing Liver in Rats with CCl4-Induced Cirrhosis - Ochenashko, O; Volkova, N; Mazur, S; Somov, A; Fuller, B; Petrenko, A (Cell transplantation. 2006; 15 (1): 23-33, 2006)
Hepatocyte transplantation is a promising method for supporting hepatic function in a broad spectrum of liver diseases. The aim of this work was to test the efficacy of human fetal liver cells to support the chronic failing liver in an experimental model of carbon tetrachloride (CCl4)-induced cirrhosis in rats. Liver cirrhosis was induced by intraperitoneal administration of CCl4 at a dose of 0.2 ml (50% v/v solution)/100 g body weight, twice a week for 3 months in rats. Ten days after stopping CCl4 administration (experimental day 0), rats received intrasplenic injection of cryopreserved fetal liver cells (FLC, 1 × 107 cells in 0.3 ml medium). As a cirrhotic control group, CCl4-induced cirrhotic rats were used with intrasplenic injection of an equal volume of medium alone. Animals were sacrificed on experimental day 15. Human fetal liver cell transplantation almost completely prevented the death of cirrhotic animals during the 2 weeks after treatment, while high ongoing mortality was seen in the cirrhotic control group. Cell transplantation into the spleen normalized total bilirubin and TBARSs levels and increased albumin levels in blood serum, as well as restoring mitochondrial function and liver detoxification function (assessed by cytochrome P450 contents and activity) compared with the activities seen in the cirrhosis control group. In parallel with this restoration of biochemical and functional liver indices, morphological patterns of liver recovery or regeneration after liver cell transplantation were demonstrated in day 15 samples by light microscopy. These were absent in the group that had received only medium alone.
Keywords: Fetal liver cells; Human; Cryopreservation; Liver cell transplantation; CCl4-induced cirrhosis; Rat liver function